Developing Cirebon Local History Teaching Materials to Increase Historical Awareness of High School Students - Candra Permana; Didin Saripudin; Nana Supriatna; Leli Yulifar (Newinera Publisher, 2026)
This research is motivated by the lack of local history content of the Cirebon Sultanate in history textbooks used at the high school level. This research aims to: (1) identify Cirebon local history teaching materials that can be integrated into high school history learning in Cirebon City; (2) formulate an initial design for Cirebon local history teaching materials; (3) develop Cirebon local history teaching materials; and (4) implement these teaching materials to increase students' historical awareness and local wisdom. This research uses the 10-step research and development method of the Borg and Gall model. The effectiveness test was conducted through a quasi-experimental method by comparing the experimental class and the control class. The results of the study indicate that the integration of local history material of the Cirebon Sultanate in high school history learning is important. The developed teaching materials have been shown to have a positive effect on increasing students' historical awareness and local wisdom in the experimental class compared to the control class. This study concludes that the Cirebon Sultanate local history teaching materials are effective for use as Cirebon local history teaching materials in high school.